2021
DOI: 10.3892/mco.2021.2265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of modulated electro‑hyperthermia for advanced metastatic breast cancer

Abstract: Modulated electro-hyperthermia (mEHT) is a new treatment modality developed to overcome the problems associated with traditional hyperthermia; mEHT uses a precise impedance-matched system and modulated radiofrequency current flow to malignant tumors. It selects the malignant cells based on their biophysical differences, due to their high metabolic rate, individual (autonomic) behavior and membrane status. The aim of the present study was to report the outcomes of mEHT in the treatment of advanced breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…This is achieved by exciting lipid rafts through mEHT-induced heating and inducing double-strand DNA breaks with radiotherapy 46 . Furthermore, studies have demonstrated the additional benefits of mEHT in conjunction with conventional therapies, leading to increased treatment response, improved overall survival, and a lack of side effects 47 49 . Thereofre, this combinatorial strategy holds the promise of not only improving the local control of tumors but also potentially minimizing side effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by exciting lipid rafts through mEHT-induced heating and inducing double-strand DNA breaks with radiotherapy 46 . Furthermore, studies have demonstrated the additional benefits of mEHT in conjunction with conventional therapies, leading to increased treatment response, improved overall survival, and a lack of side effects 47 49 . Thereofre, this combinatorial strategy holds the promise of not only improving the local control of tumors but also potentially minimizing side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The mEHT was successfully applied to advanced breast cancer [88], including triplenegative cases [89,90], and leiomyosarcoma of the breast [91]. The study of thirteen patients with complicated, advanced invasive ductal breast carcinoma, mostly triple-negative immunohistochemical status and multiple metastases, showed more than two months of median survival [92].…”
Section: Survival Timementioning
confidence: 99%
“…Modulated electro-hyperthermia (mEHT) is an advanced option in the hyperthermia field that applies a 13.56-radiofrequency electromagnetic current generated by a capacitive coupling setup between two electrodes [ 20 ]. mEHT is approved for cancer therapy in several countries, exhibiting promising results in tumor responses with no serious side effects in different cancer types [ 21 , 22 , 23 , 24 , 25 ]. One great advantage of mEHT is the non-invasiveness [ 26 ], in contrast to RFA, which requires the insertion of a needle into the tumor tissue [ 27 ].…”
Section: Introductionmentioning
confidence: 99%